African Responses to African Challenges: Reflections on State, Development and the Pandemic in Africa - Otávio, Anselmo; de Almeida, Elga Lessa; de Almeida, Elga Lessa (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2024)
The featured article proposes to reflect on the relationship between the state, the Covid-19 pandemic, and development in the African continent. In this paper, I aim to demonstrate that, in addition to symbolizing the advancement of African solidarity and seeing integration as a means to solve African challenges, the actions to mitigate the advance of Covid-19 in the African continent, in fact, reflect, to a greater or lesser extent, the African state's detachment from neoliberalism. To this end, a qualitative, interpretative approach is adopted, based on a literature review and analysis of official documents. This paper is structured, apart from the introduction and the final considerations, in three more sections. In the first, we discuss the main characteristics of the relationship between the state and economic development in Africa during the Cold War. Next, we analyze the advance of neoliberalism and its impacts on the relationship between state and development in African countries. Finally, in the third section the main objective is to highlight how African countries acted in the fight against the Covid-19 pandemic.